(3WQb GdJMdjd GdYOOj (B:s (3GdeHQeL HdZI HjSc (B/s - (3efUhQ, YhVs; (3YRGe, UHQjs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 1999)
(3GdCNWGA CfhGYgG heUGOQgG,eJSdSdGJ Gdbhi hMSGH GdOhGd,GjLGO LPhQ GdeYGOdGJ,GdeUahaGJ hGdeMOOGJ hGdeYGOdGJ GdNWjI GdBfjI,GdaQhb GdefJgjI,GdJaGVd GdYOOj hGdJcGed GdYOOjGdMd GdYOOj ddeYGOdGJ GdJaGVdjIs
(3HHdjhZQGajG(B:(3U(B.183-184s
Keywords: (3GdHQeLIs; (3GdMGSHGJ GdGdcJQhfjIs